2016
DOI: 10.1242/jeb.142216
|View full text |Cite
|
Sign up to set email alerts
|

Flying high: Limits to flight performance by sparrows on the Qinghai-Tibet Plateau

Abstract: Limits to flight performance at high altitude potentially reflect variable constraints deriving from the simultaneous challenges of hypobaric, hypodense and cold air. Differences in flight-related morphology and maximum lifting capacity have been well characterized for different hummingbird species across elevational gradients, but relevant within-species variation has not yet been identified in any bird species. Here we evaluate load-lifting capacity for Eurasian tree sparrow (Passer montanus) populations at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 34 publications
(34 reference statements)
4
32
0
Order By: Relevance
“…However, although we found no significant difference in body mass between the sexes, males had longer wings than females. These results are consistent with those obtained for other populations or other subspecies of the Eurasian Tree Sparrow (St. Louis and Barlow 1991;Mónus et al 2011;Sun et al 2016). Although sexual displays in birds require much energy (Gil and Gahr 2002;Ward and Slater 2005), male Eurasian Tree Sparrows can behave in the same intensity during autumnal sexual recrudescence as they commonly do at prebreeding (García-Navas et al 2008;Pinowski et al 2009).…”
Section: Sexual Size Dimorphism In Body Mass and Wing Lengthsupporting
confidence: 87%
See 2 more Smart Citations
“…However, although we found no significant difference in body mass between the sexes, males had longer wings than females. These results are consistent with those obtained for other populations or other subspecies of the Eurasian Tree Sparrow (St. Louis and Barlow 1991;Mónus et al 2011;Sun et al 2016). Although sexual displays in birds require much energy (Gil and Gahr 2002;Ward and Slater 2005), male Eurasian Tree Sparrows can behave in the same intensity during autumnal sexual recrudescence as they commonly do at prebreeding (García-Navas et al 2008;Pinowski et al 2009).…”
Section: Sexual Size Dimorphism In Body Mass and Wing Lengthsupporting
confidence: 87%
“…In birds, wing length is commonly considered an index of lean body mass (Nolan and Ketterson 1983), so the increased body mass at higher altitudes could be mainly the result of an increase in wing size and flight muscle (Sun et al 2016), or an increase in the size of metabolic and respiratory organs, i.e. the heart and lungs (Hartman 1955;Carey and Morton 1976;Sun et al 2016).…”
Section: Geographic and Climatic Variation In Body Mass And Wing Lengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that the body mass or body condition of Eurasian Tree Sparrows vary with life-history stage (Li et al 2008(Li et al , 2011(Li et al , 2012Zheng et al 2014) and living environment (Zhang et al 2011;Sun et al 2016Sun et al , 2017. Furthermore, male sparrows during the early breeding stage had significantly greater Hct values compared to those from the early wintering stage, whereas there were no significant differences in SCM between the two life-history stages (Zhao et al 2017).…”
Section: Open Accessmentioning
confidence: 90%
“…Either size modi cation of muscle ber or myo bril in highland birds plays an important role on heat production through shivering thermogenesis for maintenance of a constant core body temperature [17]. Various modi cations of muscle phenotype across altitudinal birds are probably associated with the ight performance in hypoxic environment for an increased size of myo bril which would produce more contractile force to prevent ightless, probably accounting for why highland tree sparrows perform a weak ight capacity [18].…”
Section: Pectoralis Variations To Highland Survivalmentioning
confidence: 99%